1979
DOI: 10.1177/002242787901600204
|View full text |Cite
|
Sign up to set email alerts
|

Racial Identity, Length of Incarceration, and Parole Decision Making

Abstract: Previous research has disclosed significant differences in the severity of sentences imposed on black and white offenders. This study investigated racial differences in black-white sentence patterns at the final stage of the criminal justice process, focusing on the actual amount of time served and the frequency of parole in a sample of 958 youthful offenders from a cohort of 1,345 consecutive admissions to a federal correctional institution.No racial differences were found in the actual amount of time served,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…At this point in the sentencing process, first-time offenders with an intellectual disability are treated differently from other offenders, that is, significantly more custodial non-parole sentences are given by the courts than those given to nondisabled offenders. Previous research has shown that two factors have a dominant influence on the decision to deny parole at sentencing: the charge that led to the incarceration, including the issues of public safety and the public's reaction to it (Elion & Megaree, 1979), and the related concept of dangerousness (Scott, 1977). The fact that people with an intellectual disability in this study were more likely to be charged with more serious crimes, may offer further support for the first factor.…”
Section: Discussionsupporting
confidence: 55%
“…At this point in the sentencing process, first-time offenders with an intellectual disability are treated differently from other offenders, that is, significantly more custodial non-parole sentences are given by the courts than those given to nondisabled offenders. Previous research has shown that two factors have a dominant influence on the decision to deny parole at sentencing: the charge that led to the incarceration, including the issues of public safety and the public's reaction to it (Elion & Megaree, 1979), and the related concept of dangerousness (Scott, 1977). The fact that people with an intellectual disability in this study were more likely to be charged with more serious crimes, may offer further support for the first factor.…”
Section: Discussionsupporting
confidence: 55%
“…These variables include age (Kruttschnitt 1980;Scott 1974;Tiffany, Avichai, and Peters 1975), gender (Bishop and Frazier 1984;Spohn, Gruhl, and Welch 1987), race (Boris 1979;Chiricos, PhiUip, and Waldo 1972;Unnever, Frazier, and Henretta 1980), and socioeconomic status (Pruitt and Wilson 1983;Radelet 1981;Swigert and Farrell 1977), and their impact on decisions made by police (Bynum, Cordner, and Greene 1982;Hepburn 1978;LaFree 1980;Pope 1978;Radelet and Pierce 1985), courts (Burke and Turk 1975;Daly 1987;Kelly 1976), and corrections (Bynum and Paternoster 1984;Carroll and Mondrick 1976;Elion and Megargee 1979;Petersen and Friday 1975;Ramirez 1983).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Once again, research conducted on the "liberation hypothesis" has found limited support for this explanatory scheme (Pope 1978;Reskin and Visher 1986;Unnever and Hembroff 1988). Alternatively, some researchers posit that although no direct discriminatory effects may be found in case dispositions, prejudicial decisions are incorporated into the earlier phases of the criminal justice process (i.e., presentence investigation report, decision to grant bail, assignment FEDER 283 of counsel) and then are used in the later decisions regarding case outcomes (Albonetti 1991;Elion and Megargee 1979;Swigert and Farrell 1977;Unnever et al 1980). Again, this conceptualization has been helpful in more fully exploring and explaining the inconsistent research findings.…”
Section: Literature Reviewmentioning
confidence: 99%